Partial insurance and investments in children - Pedro Carneiro; Rita Ginja (Uppsala University, Department of Economics, 2012)
This paper studies the impact of permanent and transitory shocks to income on parental investments in children. We use panel data on family income, and an index of investments in children in time and goods, from the Children of the National Longitudinal Survey of Youth. Consistent with the literature focusing on non-durable expenditure, we find that there is only partial insurance of parental investments against permanent income shocks, and we cannot reject the hypothesis full insurance against temporary shocks. Nevertheless, the magnitude of the estimated responses is small. A permanent shock corresponding to 10% of family income leads, at most, to an increase in investments of 1.3% of a standard deviation.
urn:nbn:se:uu:diva-191972
Keywords: D12; D91; I30; 330; insurance; human capital; consumption